THE ROLE OF PUBLIC ASSOCIATIONS IN THE IMPLEMENTATION OF OUT-OF-SCHOOL EDUCATION - Цибанюк; Tsybanyuk, Олександра; Oleksandra; Завгородня, Тетяна; Гнесь, Наталя Олександрівна; Дороніна, Тетяна; Стражнікова, Інна Василівна; Дарійчук, Сергій (Laplage em Revista (International), 2021)
The main purpose of the study is to analyze the role of public associations in the implementation of out-of-school education. The system of out-of-school education is characterized by the purposeful functioning of teaching, upbringing, development and socialization of the individual in his free time, with its special structures, connections andrelationships between elements. Out-of-school education is a systemic object both in its content and in its procedural aspects. The semantic components of out-of-school education are culture, society, nature, people. The procedural components of out-of-school education include the family, educational institutions, libraries, clubs, children's, student and organizations, societies, and the media. As a result, the role of public associations in the implementation of out-of-school education was determined.
Keywords: Pedagogy. Education. Out-of-school education. Public associations. Training